Mindset matters : understanding university teachers' well-being in a post-pandemic era in Finland - Tariq, Asma (2024)
This study aimed to explore how university teachers’ experiences affected their well-being after the pandemic by answering the following research questions, (1) What are university teachers’ experiences of how their well-being in the workplace has been affected during the post-pandemic phase? (2) What issues do university teachers identify as limiting their well-being during the post-pandemic phase? and (3) What strategies or coping mechanisms have university teachers utilised to manage their well-being in the post-pandemic workplace? To find answers to these research questions, ten university teachers across various departments at a Finnish university were interviewed using semi-structured interviews. This was a qualitative study which utilised thematic analysis taken through an inductive lens to understand university teachers’ perceptions with regard to their well-being after the pandemic. Findings showed that university teachers’ well-being in the workplace was influenced by several factors. University teachers’ well-being was mainly impacted in negative ways even after the pandemic due to the factors discussed in this study. However, university teachers’ experiences of how their well-being was influenced were highly dependent on their understanding of themselves, their conceptualisations of well-being and their previous experiences.